1995
DOI: 10.1021/bi00010a004
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of a (+)-trans-anti-Benzo[a]pyrene-DNA Adduct using NMR, Restrained Energy Minimization, and Molecular Dynamics

Abstract: The (+)-trans-anti-benzo[a]pyrene adduct formed at the N2 amino group of guanine is the major adduct found after metabolic activation of the ubiquitous carcinogen benzo[a]pyrene. The carcinogenic and mutagenic properties of the (+)-trans-anti-BP adduct, as well as related adducts, have been extensively studied. A DNA duplex containing a (+)-trans-anti-benzo[a]pyrene adduct covalently attached to the G8 nucleotide in the sequence d(CCTATGT[BP-G]CAC).d(GTGCACATAGG) was synthesized and the structure characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
120
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(127 citation statements)
references
References 27 publications
7
120
0
Order By: Relevance
“…It has been shown that carcinogen-DNA lesions are subject to strong sequence-dependent conformational polymorphisms. For example, in the 5Ј-TCGCT-3Ј sequence context of this study (ϩ)-trans-BPDE-N 2 -dG induces a structural motif characterized by Watson-Crick base pairing (7) but a single nucleotide change on the 5Ј side of the same lesion is associated with the appearance of an additional conformer (13). Similarly, acetylaminofluorene-C 8 -dG adducts have been associated with sequence-specific polymorphisms in the extent of base pair denaturation (15,18,38,45), and these variations constitute an important source of repair heterogeneity (34).…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that carcinogen-DNA lesions are subject to strong sequence-dependent conformational polymorphisms. For example, in the 5Ј-TCGCT-3Ј sequence context of this study (ϩ)-trans-BPDE-N 2 -dG induces a structural motif characterized by Watson-Crick base pairing (7) but a single nucleotide change on the 5Ј side of the same lesion is associated with the appearance of an additional conformer (13). Similarly, acetylaminofluorene-C 8 -dG adducts have been associated with sequence-specific polymorphisms in the extent of base pair denaturation (15,18,38,45), and these variations constitute an important source of repair heterogeneity (34).…”
Section: Discussionmentioning
confidence: 95%
“…The structural influence of the cytosine methyl group on B-DNA conformation seems to be insignificant as this group is located in the major groove of the DNA helix (48). In contrast, the B[a]P ring of (ϩ)-trans adducts is positioned in the minor groove and is directed toward the 5Ј end of the modified strand (49,50). BPDE forms noncovalent intercalative complexes with double-stranded DNA that are thought to precede covalent binding of BPDE to DNA (51).…”
Section: Discussionmentioning
confidence: 99%
“…29 In the TG*C sequence context, the dominant conformation is of the same MG type, but a minor conformation may involve insertion of the BP moiety into the duplex with disruption of Watson-Crick pairing at the lesion site. 30 More subtle sequence effects on the MG conformations of the 10S (+)-transanti- [BP]-N 2 -dG adduct in 5′-CG*G and 5′-GG*C sequence contexts have been recently reported 31 and have been attributed to the effects of steric hindrance between the exocyclic amino groups of guanines and the BP residues that compete for the same space in the MG. Interestingly, for the same 10S adduct in a CG*C sequence context in an 11/10-mer duplex in which the G* had no partner, a base-displaced/intercalated (BD) conformation was adopted in which the BP rings were inserted into the helix with the modified guanine residue, as well as the puckered benzylic ring positioned on the major groove side of the helix. 32 The CG*C and TG*T sequences are of unusual interest because the nature of the flanking bases affects not only the adduct conformations in double-stranded DNA, but also a number of other properties.…”
Section: Introductionmentioning
confidence: 99%